2020
DOI: 10.1093/ibd/izaa125
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Tryptase Promotes Inflammatory Bowel Disease–Induced Intestinal Fibrosis

Abstract: Background Intestinal fibrosis is the final pathological outcome of chronic intestinal inflammation without specific therapeutic drugs, which leads to ileus and surgical intervention. Intestinal fibrosis is characterized by excessive deposition of extracellular matrix (ECM). The role of mast cells (MCs), which are members of the sentinel immune cell population, is unknown in intestinal fibrosis. Methods In this study, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…The expression of α-smooth muscle actin (α-SMA) in activated fibroblasts increases. Then the fibroblasts differentiate into fibrotic-phenotype myofibroblasts, which promotes wound healing and fibrosis through the secretion of large amounts of ECM components (e.g., collagen and fibronectin) and physical contraction [ 75 ].…”
Section: Pro-allergic and Inflammatory Actions Of Mcsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of α-smooth muscle actin (α-SMA) in activated fibroblasts increases. Then the fibroblasts differentiate into fibrotic-phenotype myofibroblasts, which promotes wound healing and fibrosis through the secretion of large amounts of ECM components (e.g., collagen and fibronectin) and physical contraction [ 75 ].…”
Section: Pro-allergic and Inflammatory Actions Of Mcsmentioning
confidence: 99%
“…Although the exact relationship between inflammation and fibrosis is not clear at present, the relationship between MCs recruitment/infiltration and fibrosis has been reported in the intestines, lungs, kidneys, liver, heart and other organs [ 15 , 75 , 77 , 78 , 79 , 80 ]. In addition, toluidine blue staining showed that MCs was mostly adjacent to fibroblasts in animal skin simulating trauma and it has been found that a variety of cell surface proteins on fibroblasts can connect to the interaction between fibroblasts and MCs, such as membrane-bound stem cell factor, hyaluronic acid receptors, fibrinogen and gap-junctional intercellular communication (GJIC) [ 76 , 81 ].…”
Section: Pro-allergic and Inflammatory Actions Of Mcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, chymase can convert pro-MMP-9 to its active form MMP-9 in vitro and therefore plays a role in extracellular matrix remodeling [45]. A recent study shows the implication of tryptase in promoting IBD-induced intestinal fibrosis by activating the PAR-2/Akt/mTOR pathway in fibroblasts [46] Serine protease contribution to IBD can be described through four main mechanisms: TJ destabilization/degradation, mucus degradation, PAR activation and cytokine processing ( Figure 2).…”
Section: Serine Proteasesmentioning
confidence: 99%
“…Only PAR1 inhibition prevents 2,4,6-Trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats. Among mast cell serine proteases, tryptase was shown to activate PAR2 and the subsequent Akt/mTOR pathway, therefore promoting IBD-induced intestinal fibrosis [ 62 ]. PAR4 activation by CatG triggers altered epithelial permeability and inflammation via myosin light-chain kinase (MLCK) activation, leading to myosin light chain (MLC) phosphorylation and tight junction (TJ) destabilization [ 63 ].…”
Section: Proteases As Key Targets In Intestinal Inflammationmentioning
confidence: 99%